2008
DOI: 10.1007/s11605-007-0277-x
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective, Double-Blind, Multicenter, Randomized Trial Comparing Ertapenem 3 Vs ≥5 Days in Community-Acquired Intraabdominal Infection

Abstract: Severe secondary peritonitis is diagnosed in only 20-30% of all patients, but studies to date have persisted in using a standard fixed duration of antibiotic therapy. This prospective, double-blind, multicenter, randomized clinical study compared the clinical and bacteriological efficacy and tolerability of ertapenem (1 g/day) 3 days (group I) vs >or=5 days (group II) in 111 patients with localized peritonitis (appendicitis vs non-appendicitis) of mild to moderate severity, requiring surgical intervention. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 29 publications
0
51
0
Order By: Relevance
“…Basoli et al, who randomly assigned 90 patients with mild-to-moderate intraabdominal infection to either 3 days or 5 or more days of ertapenem therapy, found no between-group difference in infectious outcomes. 17 Those findings, however, are not generalizable to the majority of patients with intraabdominal infection, since half the patients had appendiceal disease and the overall rate of infectious complications was less than 10%. As compared with these studies, the STOP-IT trial had several advantages, including a larger sample size, randomized design, and enrollment of patients with a broader range of severity of illness.…”
Section: Discussionmentioning
confidence: 91%
“…Basoli et al, who randomly assigned 90 patients with mild-to-moderate intraabdominal infection to either 3 days or 5 or more days of ertapenem therapy, found no between-group difference in infectious outcomes. 17 Those findings, however, are not generalizable to the majority of patients with intraabdominal infection, since half the patients had appendiceal disease and the overall rate of infectious complications was less than 10%. As compared with these studies, the STOP-IT trial had several advantages, including a larger sample size, randomized design, and enrollment of patients with a broader range of severity of illness.…”
Section: Discussionmentioning
confidence: 91%
“…Many prior RCTs of treatment duration in non-bacteraemic infections have required that all patients complete the short-arm duration of treatment, with evidence of clinical improvement, prior to randomisation to prolonged treatment versus treatment discontinuation [19,20]. However, in the current survey, measures of host response to treatment (fever, vasopressor requirements and mechanical ventilation dependence) exhibited only a mild impact on antibiotic treatment recommendations, thereby suggesting that patients could be randomised at the time of bacteraemia diagnosis.…”
Section: Discussionmentioning
confidence: 72%
“…Outcomes of the two groups were similar, but the duration of antimicrobial therapy was 5.9 d in the five-day treatment group and 4.3 d in the group with no set duration of therapy (p = 0.014). More recently, Basoli et al found similar outcomes for three days of ertapenem versus five or more days of ertapenem in the management of 90 patients with IAI of moderate severity, related principally to appendicitis, who were randomized to either regimen [11]. There were no deaths in either group, and there were a total of eight infectious complications, with no difference in the incidence of complications in the two treatment groups.…”
Section: Discussionmentioning
confidence: 93%